Cultural ecologies of the land - Dillon, Patrick, 1950- author. Link
1 online resource
Keywords: "Cultural Ecologies of the Land is a radical and challenging reassessment of the way we relate to the land and to infrastructure. There was a time when the land defined us. Now, with each passing year, we are increasingly detached from it. It was once the centre stage of humanity, now it is the setting for a technological drama. What has happened, and why does it matter? This book is a multi-layered account of people and environment shaping each other through cumulative, moment-to-moment, day-to-day change, and a template for thinking about place, locality, belonging, and identity. Cultural Ecologies of the Land presents the existential crisis that many believe we now face as a systemic problem, arising from social institutions and forms of behaviour that have been marginalised with our dependency on modern infrastructure. It explains the part people have played in contributing to the crisis, and how regenerating relationships with the land offers a route towards alleviating it. This is not only about acknowledging our impact on Earth, but also understanding ourselves in relation to it, how we engage with our surroundings, make sense of them, live and work in them, and create narratives that connect and sustain us"--